HUMANISME PENDIDIKAN PAULO FREIRE DALAM IMPLEMENTASI SEKOLAH INKLUSI BAGI SISWA ANAK BERKEBUTUHAN KHUSUS - Fitri Amalia Majid; Azima Wahidatu Wildana; Yuliana Nurul Islami (LPPM STAI Muhammadiyah Probolinggo, 2026)
Inclusive education is an effort to realise educational justice for all learners, including children with special needs. However, the practice of inclusive education continues to face various challenges, including stigma, discrimination, and the limited participation of students with special needs in the learning process. This study aims to analyse the relevance of Paulo Freire’s educational humanism to the implementation of inclusive schools, examine the manifestation of the values of dialogue, humanisation, critical consciousness, and liberation, identify the supporting and inhibiting factors in its application, and analyse its contribution to the participation, empowerment, and development of the potential of students with special needs. This study employs a qualitative approach using library research. Data were obtained from Paulo Freire’s works, scholarly articles, academic books, and relevant previous studies, and were then analysed using content analysis techniques. The findings indicate that Paulo Freire’s educational humanism has strong relevance to inclusive education, as both emphasise respect for human dignity, equality, and participation. The values of dialogue, humanisation, critical consciousness, and liberation play an important role in creating an inclusive learning environment and supporting the empowerment of students with special needs. The successful implementation of these values is influenced by teacher competence, school culture, and policy support, while social stigma and traditional learning paradigms remain the main obstacles. Therefore, Paulo Freire’s educational humanism can serve as a philosophical foundation for developing inclusive schools that are more humane, democratic, and socially just.